Fluid Filtration Analysis of Complex Fractured System Based on Geomechanical Parameters and Diagenetic Alterations; 81st EAGE Conference and Exhibition 2019 - Uzhegova Yu. A. Yuliya Andreevna; Garcia B. A. U. Balsa Aura Samid; Konoshonkin D. V. Dmitriy Vladimirovich; Krasnoshchekova L. A. Lubov Afanasievna (2019, 2019)
Title screen